PENGARUH FINANCIAL LEVERAGE, AKTIVITAS, DAN PROFITABILITAS TERHADAP TERURN SAHAM, DENGAN FIRM SIZE SEBAGAI VARIABEL KONTROL (Pada Perusahaan LQ45 Yang Tergabung Dalam Bursa Efek Periode 2010-2013) - B11111058, NOVIANA (Jurnal Manajemen Update, 2015)
This study is aimed to analyze the influence of Financial Leverage, Activity, Profitability and Firm Size on the Stock Return in the company with index of LQ45 registered in Indonesia stock exchange within the periods of 2010-2013. Debt to equty ratio (DER), Total Asset Turnover (TATO), Return on Equity (ROE), and Firm Size are measured by analyze the financial statements of the company LQ45 listed in Indonesia stock exchange in the years of 2010-2013. This research applied secondary data i.e. the company financial statements the samples used were obtained from Indonesian capital Market Directory (ICMD) and IDX. This study employed purposive sampling, data collecting was conducted by determining the criteria of sampling that would yield 18 LQ45 companies during 4 years of observation. The study hypothesis was examined by utilizing the multiple linear regression analysis model. Based on the research result employing the analysis model of multiple linear regression, it was found that Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Return on Equity (ROE) do not have any significant influence on the stock return. However Firm Size has a significant influence on the Stock Return. Key words : Stock Return, Financial Leverage (DER), Activity (TATO), Profitability (ROE), and Firm Size